Comparison of polytechnic based bridging education programmes and models in Aotearoa/New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Adult Education at Massey University - Coltman, David William (Massey University, 2004)
Bridging education programmes enable under-qualified students to gain qualifications to enter tertiary courses and the workforce. These programmes have been developed in the polytechnic sector at institutional levels and without national co-ordination. This project seeks to compare and contrast features of bridging education provision in polytechnics in Aotearoa/New Zealand through information that was sought from staff and students involved in these programmes by way of recorded interviews. Materials, including course descriptions and programme handbooks, have been collected and the common content, themes and philosophies drawn out and presented. Observation by the researcher has also been used to complement and supplement the material sourced. The purpose of this study is to gather information about these bridging programmes and analyse how staff and students see them working. By mapping the sector, much of the good practice that has been developed over the many years the programmes have been offered can be drawn out. Documenting where the polytechnic sector is at in its delivery of bridging education programmes will enable practitioners to reflect on their own practice and will assist policy makers with their understanding of current practices. Benseman and Russ (2001) were able to define many of the diverse characteristics of bridging education provision in New Zealand. As with much good research their findings left the sector asking more questions than before they published. This paper also builds from this research and asks the following questions of participants in the polytechnic context: • What is the purpose of bridging education? • How is bridging education being delivered in four polytechnics/institutes of technology in Aotearoa/New Zealand? • Who is involved in bridging education, as staff, and as students? • What are the theoretical perspectives that underpin bridging education delivery in polytechnics/institutes of technology in Aotearoa/New Zealand? The project identified a number of diverse models of delivery and advocates the need for programmes that focus on purpose and product rather than standardised content. The skills of staff, and their knowledge of bridging education was not consistent across the institutions included in this study. A perceived need by stakeholders for a centralised and co-ordinated approach to bridging education provision at both institutional and at national level also became apparent through the study.
Keywords: New Zealand; Developmental studies programs